The role of sodium intake and liquid balance to overcoming breathing based on respiration rate (RR) on congestive heart failure (CHF) patients - Rijanti Abdurrachim; Nana Chairunnisa (Alma Ata University Press, 2020)
Background : Congestive Heart Failure (CHF) is the inability of the heart to pump blood to meet the needs of oxygen and nutrients to the body's tissues. The most common symptom of recurrence is shortness of breath. One of the dietary management of CHF patients is the limitation of sodium and fluid. The aim of the study was to determine the role of sodium intake and fluid balance in the occurrence of shortness of breath based on Respiration Rate (RR) in Congestive Heart Failure (CHF) patients in Cardiac Hospitalization at H. Moch. Ansari Saleh Banjarmasin. Method: This type of determination is an observational analytic with a prospective approach. The population was all CHF patients who were hospitalized in the Diamond Room and Kumala Room 3rd Floor RSUD H. Moch. Ansari Saleh Banjarmasin from April 16 to May 6, 2018. Samples were 12 people taken based on inclusion and exclusion criteria. How to collect data using a 1x24 hour food recall form, a liquid form and a Respiration Rate form . Data Analyst is using the Spearman rank correlation test with a 95% confidence level. Results : 12 respondents obtained 58.3% aged 56-65 years, 66.7% male sex, and 50% with junior and senior high school education or equivalent. The nutritional assessment of CHF patients is reduced breathlessness, decreased blood pressure, normal laboratory data, and no changes in dietary material were given . A sufficient sodium intake (75%), a negative fluid balance level of 66.7%, occurrence of shortness of breath based on normal RR (50%) and tachypnea (50%). Conclusion : There is a correlation between sodium intake (p = 0.049) and fluid balance (p = 0.01) to the occurrence of shortness of breath based on the RR value of CHF patients in the Cardiovascular Inpatient Hospital Dr.H.Moch.Ansari Saleh Banjarmasin.Adjusting sodium intake and fluid balance is useful to reduce symptoms of shortness of breath in CHF patients.